A comprehensive synthesis of dung beetle records (Coleoptera, Scarabaeidae, Scarabaeinae) from Sabah, Malaysia - Yim, Marx W. H. (2024)
Dung beetles play key roles in terrestrial ecosystems, contributing to many important ecosystem process and functions, such as nutrient recycling, parasite control and seed dispersal. Due to their tight associations with mammals and their responses to environmental change, they are also frequently used as environmental and biological indicators. Despite their importance, knowledge about dung beetles in Southeast Asia is limited. To address this information gap, we established a databasing project - “Mobilising data on ecologically important insects in Malaysia and Singapore” - funded by the Global Biodiversity Information Facility (GBIF). As part of this project, we compiled two extensive datasets – a sampling-event and occurrence dataset and a taxonomic checklist – for the dung beetles of Sabah, Bornean Malaysia. The sampling-event dataset documents 2, 627 unique sampling events and 21, 348 dung beetle occurrence records for Sabah. The taxonomic checklist includes 156 confirmed dung beetle species and 36 synonyms, totalling 192 records. These datasets have been made open access through the GBIF portal, which we hope will enhance the understanding of dung beetle taxonomy and their distributions in Southeast Asia.